Please come to the show - Senior, David; Exhibition Research Centre, Liverpool; Museum of Modern Art Library, New York ([London] : Occasional Papers, 2014)
"David Senior, bibliogrpaher at the Museum of Modern Art library in New York, selects a wide range of exhibiton-related ephemera--invitations, flyers and posters form the 1960s to the present--and presents them here as an historically overlooked but integral aspect of exhibitions. Often the first point of contact between audience and artist, exhibition epherema is an essential lexicon for graphic designers, curators, art hitorians and anyone intereseted in the event-based nature of showing art."--Back cover.
Published on the occasion of 'Please Come to the Show,' an exhibition at the Exhibition Research Centre, Liverpool, 13 February-11 April 2014, first shown at the Museum of Modern Art Library, New York, 8 May-23 September 2013
boek